Poor health and social outcomes for ex‐prisoners with a history of mental disorder: a longitudinal study. (24th June 2014) - Cutcher, Zoe; Degenhardt, Louisa; Alati, Rosa; Kinner, Stuart A.
Abstract Objective: To examine the association between self‐reported lifetime diagnosis of mental disorder and health‐related outcomes in prisoners during the first six months after release. Methods: We interviewed 1, 324 adult prisoners in Queensland, Australia, within six weeks of expected release and one, three and six months post‐release. Outcomes of interest included health service access, housing, employment, substance use and criminal activity. We used multivariate logistic regression to investigate the association between self‐reported, lifetime diagnosis of mental disorder and these health‐related outcomes post‐release, adjusting for pre‐existing disadvantage. Results: 43.4% of participants reported a lifetime diagnosis of mental disorder. This group had increased crude odds of poor outcomes across all evaluated domains. After adjusting for pre‐existing disadvantage, significantly increased odds of poor outcomes persisted in the substance use, mental health, crime and health service access domains. Conclusions: People with a history of mental disorder experience particularly poor outcomes following release from prison that are not fully explained by pre‐existing disadvantage. Implications: Evidence‐based transitional programs for prisoners with a history of mental disorder should be provided at a level commensurate with need.